S-Generalized supplemented modules - B. H. Al-Bahrany; A. J. Al-Rikabiy (مجلة بغداد للعلوم, 2024)
Xue introduced the following concept: Let M be an R- module. M is called a generalized supplemented module if for every submodule N of M, there exists a submodule K of M such that M = N +K and N Ç K Í Rad(K).